2014
DOI: 10.1177/1470320314549221
|View full text |Cite
|
Sign up to set email alerts
|

The association between angiotensin-converting enzyme 2 polymorphisms and essential hypertension risk: A meta-analysis involving 14,122 patients

Abstract: Background: Some studies have evaluated the associations between the angiotensin-converting enzyme 2 (ACE2) gene polymorphisms and essential hypertension (EH) risk. However, the results remain uncertain. We carried out a meta-analysis to derive a more comprehensive estimation of these associations. Methods: Case-control studies were identified by searching PubMed, EMBASE, Chinese National Knowledge Infrastructure (CNKI) and Wangfang databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 18 publications
(29 reference statements)
0
50
0
2
Order By: Relevance
“…ACE2, coded on Xp22 at the location where genes are known to escape X-inactivation, which may contribute to the phenotypic differences between sexes and the tissue-specific differences in Xinactivation [20]. An intronic variant of ACE2 (rs2285666, also known as G8790A) has been associated with hypertension [21]. Wu YH et al reported that the serum ACE2 level in individuals with AA genotype was 1.5-fold higher [22].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2, coded on Xp22 at the location where genes are known to escape X-inactivation, which may contribute to the phenotypic differences between sexes and the tissue-specific differences in Xinactivation [20]. An intronic variant of ACE2 (rs2285666, also known as G8790A) has been associated with hypertension [21]. Wu YH et al reported that the serum ACE2 level in individuals with AA genotype was 1.5-fold higher [22].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this gender-specific contribution may reflect the impact of some genes on sex chromosomes, such as apelin and angiotensin-converting enzyme 2 in X chromosome [24]. Several lines of evidence have suggested a heterogeneous contribution of these X-linked genes to the pathogenesis of hypertension [15, 2527]. In spite of the null association of apelin gene with hypertension in this study, we observed that SBP differed significantly between two homozygous genotypes of rs3761581 in apelin gene.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it also improved left ventricular remodeling and function in a rat model with diabetic cardiomyopathy [Dong et al 2012]. Furthermore, SNPs in the ACE2 gene are also associated with LVH, impaired cardiac function and HT Wang et al 2013;Yang et al 2014]. Because of these and other findings, ACE2 gene is considered a functional candidate for CVD [Burrell et al 2013].…”
Section: Ace2 In Cardiac Remodelingmentioning
confidence: 99%